Case Report: Proteinase 3 Antineutrophil Cytoplasmic Antibody-Associated Ulcerative Colitis Presenting as Recurrent Intestinal Pseudo-Obstruction in a Teenage Patient With in situ Proteinase 3 Immunohistochemical Staining - Yang, Ching-Wen; Kao, Yu-Chien; Lin, Pei-Chun; Chien, Hsi-Yuan; Lin, Sheng-Chieh; Lee, Yu-Hsien; Huang, Yen-Lin; Fang, Shiuh-Bin (Frontiers in Pediatrics, 2022)
Ulcerative colitis (UC) is a chronic relapsing inflammatory bowel disease with the colorectum as its major target organ. Involvement of the upper gastrointestinal tract in UC is rare and presents with nonspecific endoscopic and microscopic characteristics. Recent studies have demonstrated proteinase 3 antineutrophil cytoplasmic antibody (PR3-ANCA) to be a serological marker for differentiating UC from Crohn’s disease in children and for detecting disease activity and nonresponse to steroid therapy and antitumor necrotizing factor-α agents. Herein, we report a 13-year-old female patient mainly presenting with recurrent bilious vomiting who was initially diagnosed with acute gastroenteritis. Intestinal pseudo-obstruction was confirmed through observation of a patent but segmentally dilated jejunum in the barium follow-through examination and other imaging; such obstruction can be attributed to backwash ileitis, superior mesenteric syndrome, ileus due to hypokalemia, or PR3-associated enteritis. Laboratory data revealed leukocytosis with neutrophil predominance and serum antinuclear antibody and PR3-ANCA positivity. Overlapping syndrome with autoimmune diseases was suspected. Pathology revealed a crypt abscess with aggregates of neutrophils consistent with UC but did not indicate vasculitis. The in situ immunohistochemical staining revealed PR3 density mainly in the colon and focally in the duodenum. To our knowledge, this is the first case report with in situ pathological evidence of PR3 in inflamed intestinal tissues in a patient with UC and with rare initial presentation of intestinal pseudo-obstruction–induced recurrent bilious vomiting. Whether the clinical features of the present case constitute overlap syndrome with other autoimmune disease or a disease variation of UC warrants further investigation. Notably, the patient’s serum PR3-ANCA titers remained high in coincidence with increased disease activity and nonresponse to steroid therapy, but became lower after infliximab treatment. PR3-ANCA as a potential serum biomarker to aid in making differential diagnoses of UC in children, correlating disease activity, and predicting therapeutic responses was also reviewed.